Immuno Affinity SELEX for Simple, Rapid, and Cost-Effective Aptamer Enrichment and Identification against Aflatoxin B1 - Setlem, Keerthana; Mondal, Bhairab; Ramlal, Shylaja; Kingston, Joseph (Frontiers in Microbiology, 2016)
Aflatoxins are naturally occurring mycotoxins that contaminate food and agro commodities, leading to acute and chronic health conditions in human and animals. In the present work, an attempt was made to generate high-affinity single stranded DNA (ssDNA) aptamers that specifically bind to Aflatoxin B1 (AFB1) by a modified Systemic Evolution of Ligands by Exponential Enrichment (SELEX) procedure with the aid of Immunoaffinity (IA) columns. Ten rounds of SELEX and alternating three counter SELEX rounds with a cocktail of related and other mycotoxins were performed to enhance the specificity. Resultant 105 aptamers were clustered into 12 groups according to their primary sequence homology. Candidates with lowest Gibbs free energy (dG value) and unique stem loop structures were selected for further characterization. Aptamers, AFLA5, AFLA53 and AFLA71 exhibiting lower Kd values (50.45±11.06 nM, 48.29±9.45 nM, and 85.02±25.74 nM) were chosen for development of ELONA and determination of purification ability of toxin. The detection limit (LOD) of AFLA5 and AFLA71 was 20 ng/ml and 40 ng/ml respectively. HPLC analysis implied that selected aptamers were able to recover and quantify 82.2 to 96.21 % (LOQ - 53.74 ng) and 78.3 to 94.22 % (LOQ - 66.75 ng) of AFB1 from spiked corn samples, respectively. These findings indicate, immunoaffinity based SELEX can pave an alternative approach to screen aptamers against mycotoxin detection and purification.